1997
DOI: 10.1104/pp.115.4.1691
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Microbial Genes for Pathogenesis and Symbiosis by Chemicals from Root Border Cells

Abstract: Reporter strains of soil-borne bacteria were used to test the hypothesis that chemicals released by root border cells can influente the expression of bacterial genes required for the establishment of plant-microbe associations. Promoters from genes known to be activated by plant factors included vir€, required for Agrobacferium fumefaciens pathogenesis, and common nod genes from Rhizobium leguminosarum bv viciae and Rhizobium melilofi, required for nodulation of pea (Pisum sativum) and alfalfa (Medicago safivu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
24
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 37 publications
0
24
0
Order By: Relevance
“…However, the primary source of exudates in most species is not the region of elongation but the root tip itself (Griffin et al 1976;McDougall and Rovira 1970;Schroth and Snyder 1961). In addition, the release of specific products-such as flavonoids, that influence infection by symbiotic bacteria and fungi-also predominates at the root tip rather than at the site of infection behind the root tip (Peters and Long 1988;Zhu et al 1997). If exudation patterns do play a role in localized root infection, then altering root exudation could be predicted to result in a change in infection patterns.…”
Section: Introductionmentioning
confidence: 96%
“…However, the primary source of exudates in most species is not the region of elongation but the root tip itself (Griffin et al 1976;McDougall and Rovira 1970;Schroth and Snyder 1961). In addition, the release of specific products-such as flavonoids, that influence infection by symbiotic bacteria and fungi-also predominates at the root tip rather than at the site of infection behind the root tip (Peters and Long 1988;Zhu et al 1997). If exudation patterns do play a role in localized root infection, then altering root exudation could be predicted to result in a change in infection patterns.…”
Section: Introductionmentioning
confidence: 96%
“…Border cells can act by forming a boundary that inhibits accumulation of certain bacteria or alternatively by attracting and providing nutrients to other bacteria species (Hawes et al, 1998). Furthermore, Zhu et al (1997) have demonstrated that chemicals released by root border cells can regulate the expression of bacterial genes required for the establishment of plant-microbe associations.…”
mentioning
confidence: 99%
“…These cells, termed border cells for their ability to form a protective border around the root tip, are separate from the root, but appressed to it by a water-soluble polysaccharide matrix (Hawes et al, 2000). Border cells are much more than by-products of root cap growth and have been shown to attract and immobilize nematodes, produce defence structures in response to fungi, bind and repel bacteria, and increase mucilage production in response to aluminum (Zhu et al, 1997;Hawes et al, 2000;Miyasaka & Hawes, 2001;Woo et al, 2004;Humphris et al, 2005). Border cells appear within 48-72 hours after germination (Colour Plates 11.2a, b, c and d) and once a species-specific number of border cells are produced, root cap turnover ceases and border cells remain appressed to the root until exposed to water.…”
Section: Spatially Resolved Metabolomics Of Alfalfa (Medicago Sativa)mentioning
confidence: 99%